Integrating educational in the creative English language classroom: With reference to the United Nations Sustainable Development Goals - Atoboyeva Aziza Muhiddin qizi; Eshmirzayeva Nozima Bahodir qizi (Genius Journals, 2023)
In this article the main approach of SDG and its features, moreover educational growth will be analyzed. As it is vivid that educational progress is so vital for everyone. However, sometimes we confront a number of issues relating to the education. It has been considered that every field is based on the other. Integrating so creative English classroom is so important, as we can grab students’ attention. The reason why in some countries the status of education is so low is owing to lack of highly qualified teachers and the students who can not do any international research in their field.
Keywords: Educational Growth; Educational Progress; Integrating so creative English classroom